Antimicrobial Capacity and Oxidant-Antioxidant Properties of Methanolic Extracts from Tricholoma Caligatum Wild Edible Mushroom - K. GEZER; O. KAYGUSUZ; E. N. HERKEN; A. ERMIŞ; M. KAYGUSUZ; Y. SALDIR; U. SOYLU (International Journal of Secondary Metabolite)
Consumption of mushroom has increased remarkably due to their desirable aroma, taste and high nutritional content. This study was undertaken to measure and compare the total phenolic content, total oxidant status, total antioxidant capacity, lipid hydroperoxides and total free sulfhydryl levels of methanol extract of Tricholoma caligatum. The antimicrobial effect of methanol extract of T. caligatum was tested against three species of Gram-positive bacteria (Micrococcus luteus NCIBM, Staphylococcus aureus ATCC 25923 and Bacillus subtilis ATCC 6633), three species of Gram-negative bacteria (Proteus vulgaris RSKK 96026, Escherichia coli ATCC 35218 and Yersinia enterecolitica RSKK 1501) and one species of yeast (Candida albicans ATCC 10231) by agar disc diffusion method. The results of this study shows that T. caligatum demonstrated a strong antioxidant and antimicrobial activity. It suggests that the mushroom can potentially be used as a source of natural antioxidants and for pharmaceutical purposes in treating of various diseases.